A Multiplex Approach to Molecular Detection of Brucella abortus and/or Mycobacterium bovis Infection in Cattle - Sreevatsan, Srinand (American Society for Microbiology, 2000)
A multiplex amplification and detection platform for the diagnosis of Mycobacterium bovis and Brucella abortus infection simultaneously in bovine milk and nasal secretions was developed. This system (designated the bovine pathogen detection assay [BPDA]-PCR) consists of duplex amplification of species-specific targets (a region of the BCSP31K gene of B. abortus and a repeat-sequence region in the hsp65 gene of M. bovis, respectively). This is followed by a solid-phase probe capture hybridization of amplicons for detection. On the basis of spiking experiments with normal milk, the analytical sensitivity of the assay was 800 CFU equivalents/ml of milk for B. abortus and as low as 4 CFU equivalents per ml of milk for M. bovis. BPDA-PCR was validated with 45 liver samples from lemmings experimentally infected with B. abortus. The assay sensitivity, based on culture status as a “gold standard,” was 93.9%. In this experiment, BPDA-PCR also identified five culture-negative liver samples as positive (41.7%). Field studies for the evaluation of BPDA-PCR were performed with samples from dairy animals from geographically distinct regions (India, Mexico, and Argentina). A high prevalence of shedding of B. abortus (samples from India) and M. bovis (samples from Mexico) was identified by BPDA-PCR. In samples from India, B. abortus shedding was identified in 86% of milk ring test-positive animals (n = 15) and 80% of milk ring test-negative cows (n = 5). In samples from Mexico, M. bovis was identified by PCR in 32.6% of pools (n = 46) of milk that each contained milk from 10 animals and in 56.2% of nasal swabs (n = 121) from cattle from tuberculin test-positive herds. In contrast, the Argentine cattle (n = 70) had a modest prevalence of M. bovis shedding in nasal swabs (2.9%) and milk (1.4%) and of B. abortus in milk (11.4%). On the basis of these analyses, we identify BPDA-PCR as an optimal tool for both screening of herds and testing of individual animals in a disease eradication program. A combination of the duplex assay, screening of milk samples in pools, and the proposed algorithm provides a highly sensitive, cost-effective, and economically viable alternative to serological testing.